Managing the environment, managing ourselves : a history of American environmental policy - Andrews, Richard N. L. (New Haven : Yale University Press, 2020)
In the third edition of this definitive book, Richard N.L. Andrews looks back at four centuries of American environmental policy, showing how these policies affect contemporary environmental issues and public policy decisions, and identifying key policy challenges for the future. Andrews crafts a detailed and contextualized narrative of the historical development of American environmental policies and institutions. This volume presents an extensively revised text, with increased detail on the fifty-year history of the modern environmental policy era and is updated through the Obama and Trump administrations.
Frontmatter -- Contents -- Preface to the Third Edition -- Acknowledgments -- 1. Introduction: Environment and Governance -- 2. Who Owns the Environment? Historical Context and Colonial Precedents -- 3. The Constitutional Framework -- 4. Land and Transport: Commercial Development as Environmental Policy -- 5. Industrialization, Resource Differentiation, and Public Resource Management -- 6. Public Health and Urban Sanitation -- 7. The Progressive Era -- 8. Conservative "Normalcy" and New Deal Conservation -- 9. Superpower and Supermarket -- 10. The Rise of Modern Environmentalism -- 11. Toward a National Environmental Policy -- 12. The EPA: Nationalizing Pollution Control -- 13. Public Lands and Wildlife Conservation -- 14. Agricultural and Urban Environmental Management -- 15. Energy Policy and Climate Change -- 16. Environmental Policy in a Global Economy -- 17. The Trump Agenda -- 18. Man aging the Environment, Managing Ourselves -- Chronology -- Notes -- Index
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on February 25, 2020).
JSTOR
Keywords: Environmental policy -- United States -- History; Environmental management -- United States -- History; Environnement -- Politique gouvernementale -- États-Unis -- Histoire; Environnement -- Gestion -- États-Unis -- Histoire; POLITICAL SCIENCE -- Public Policy -- Environmental Policy; Environmental management; Environmental policy; United States; History